Teaching NeuroImage: Branching Dura Mater in Primary CNS ALK-Positive Anaplastic Large Cell Lymphoma - Wanakorn Rattanawong; Arnant Tekarnjnavanit; Chayoot Marukatat; Pasin Hemachudha; Thanakit Pongpitakmetha; Prakit Anukoolwittaya (My University, 2023)
A 22-year-old male presented with the new onset of gradually progressive diffuse headache for 2 months.He exhibited no apparent physical and neurological abnormalities except limited bilateral lateral rectus movement and bilateral papilledema on fundoscopic examination.The MRI showed multiple nodular enhancing lesions along both sides of the falx cerebri with perilesional edema.Additionally, these nodular structures formed a branching network of thickening dura mater to adjacent nodular structures (Figure 1).Due to the atypical features of dura mater, the differential diagnosis included tuberculosis, sarcoidosis, IgG4-related disorders, lymphoproliferative disorders, meningioma, hemangiopericytoma, and Erdheuim-Chester disease.(1) A stereotactic biopsy was performed.The pathological and immunohistochemistry results, as well as systemic evaluation, were compatible with primary central nervous system anaplastic large cell lymphoma with ALK+.(2) After the total of six courses of high-dose methotrexate and ifosfamide followed by whole-brain radiation, the patient achieved complete remission and resolution of headache (Figure 2).
Keywords: Anaplastic large-cell lymphoma; CNS Lymphoma Diagnosis and Treatment